Taṭwīr Masyrū' al-Mudawwanah As-Sam'iyyah al-Baṣariyyah li Kafā`ati at-Tafkīr an-Nāqid wamā warā`a al-Ma'rifī li Firaqi al-Munaẓarah al-‘Arabiyyah fī Indonesia - Muhammad Ahsan Thoriq; Mohammad Ahsanuddin; Nurul Murtadho; Walaa Ali Omar Abdelzaher (LISANIA: Journal of Arabic Education and Literature, 2023)
This research aims to develop an Arabic audio-visual debate corpus based on the Qatar debate guidelines. This development is intended to assist students in enhancing critical thinking and metacognitive skills through Arabic debate learning. The research utilizes the Lee & Owens development approach and is implemented using experimental and control groups. The choice of this approach is because it focuses solely on multimedia learning development. The development procedure consists of five stages: analysis, design, development, implementation, and evaluation. The subjects in this study consist of 32 students participating in the Arabic debate club. The research results show that the average N-gain score of the experimental group after using the researcher-provided learning corpus increased significantly compared to the control group. Respondents were interested in the provided learning corpus, enabling them to think critically and quickly. The use of the learning corpus in the teaching and learning process is beneficial for students to enhance learning focus and accelerate critical thinking in expressing arguments in Arabic debates. The learning corpus can be implemented in various educational fields. Visual learning is remembered and exemplified more quickly by learners. Learning using the corpus can enhance critical thinking and determine students' metacognitive abilities to solve a problem.